Third Five Year Plan Volume III : Industries and Transport - Planning Commission, Government of India (Planning Commission, Government of India, 1961)
The Third Five-Year Plan outlines a comprehensive strategy for strengthening industries and transport infrastructure in Uttar Pradesh, emphasizing balanced growth across large, medium, and small-scale sectors. Major initiatives include expansion of the Government Cement Factory at Churk, establishment of the U.P. Heavy Industries Corporation, development of industrial estates in Gorakhpur, Mirzapur, and Ghaziabad, and reorganization of geology and mining operations to enhance mineral resource utilization. Simultaneously, the Plan places strong emphasis on promoting small-scale and cottage industries, particularly handloom and handicrafts, through weaver colonies, training programs, processing facilities, and financial support mechanisms. Quality improvement is prioritized via the expansion of the Quality Marking Scheme and establishment of inspection depots to standardize products and enhance export potential. Marketing and promotional efforts—including advertisements, mobile sales units, tourist showcases, and rural craft museums—are designed to improve market access and artisan incomes. Significant investments are also directed toward sericulture and eri culture expansion, cooperative development, and infrastructural support such as rural roads, bridges, and tourism facilities. By integrating industrial growth with transport modernization and artisan welfare, the Plan aims to generate employment, strengthen regional production capacities, and position Uttar Pradesh as a dynamic contributor to India’s broader economic development.
Planning Commission, Government of India
Keywords: Third Five Year Plan- Industries and Transport; Industrial Development in Uttar Pradesh; Large and Medium Industries; Small Scale Industries; Mineral Development; Industrial Estates Development; Handloom Industry Promotion; Handicrafts Marketing Initiatives; Sericulture Expansion